2020
DOI: 10.3390/ijerph17228637
|View full text |Cite
|
Sign up to set email alerts
|

Are Loneliness and Social Isolation Associated with Quality of Life in Older Adults? Insights from Northern and Southern Europe

Abstract: Purpose: Loneliness and social isolation have detrimental effects on health in old age; however, the prospective associations with quality of life (QoL) remain unclear. Furthermore, despite the existence of a European north-south gradient in the distribution of loneliness and social isolation, little is known whether the associations are context-specific. We investigated the relationships between loneliness, social isolation and QoL of older adults residing in the North (Sweden) and South (Spain) of Europe. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…High adherence to self-isolation recommendations, combined with a decrease in physical contact with loved ones, puts older adults at risk of social isolation. Social isolation presents a major modern-day challenge and has been associated with several negative health outcomes, such as depression [19], frailty [20], cognitive decline [21] and low quality of life [22,23].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…High adherence to self-isolation recommendations, combined with a decrease in physical contact with loved ones, puts older adults at risk of social isolation. Social isolation presents a major modern-day challenge and has been associated with several negative health outcomes, such as depression [19], frailty [20], cognitive decline [21] and low quality of life [22,23].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Chruściel et al [51] showed that living with older adults' relatives may be expected to be favorable for older adults because it translates into better physical, psychological and social domains. Also, loneliness, which frequently accompanies old age, leads to the deterioration of the QOL [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Active Ageing Index report [ 31 ], Spain and Portugal have a similar and much higher Gini index of inequality than Sweden, and the active ageing index is in fact higher in Sweden, whereas in Spain and Portugal the index is similar [ 31 ]. Additionally, the association between QoL and social factors, such as loneliness and social isolation, also differs between Sweden and Spain [ 32 ].…”
Section: Discussionmentioning
confidence: 99%